Social representations of primary teachers in relation to the teaching and learning process of reading and writing (Research, Society and Development, 2020)
The purpose of this research was to analyze the social representations in primary school teachers in relation to the teaching and learning process of reading and writing present in the I.E. N ° 80819 Francisco Lizarzaburu - El Porvenir. The research was mixed. The interpretive method was used, under a field and descriptive modality. The collection techniques were the interview and the content analysis. We rely on the quantitative analysis to calculate the data of the structural analysis based on the Theory of Social Representations of Moscovici (1979). The key informants were six primary level teachers and the principal of the campus. The core of social representation in teachers about the teaching and learning process is revealed as a set of complex elements whose practice has formative and introspective implications of an important level of difficulty. This highlights methodological and experiential limitations within the educational organization to which they belong that directly affects their inventiveness and creativity